The Oxford handbook of World Englishes - Filppula, Markku Ed.; Klemola, Juhani; Sharma, Devyani, 1976- (New York : Oxford University Press, 2017)
" As the most widely documented language in human history English holds a unique key to unlocking some of the mysteries of the uniquely human endowment of language. Yet the field of World Englishes has remained somewhat marginal in linguistic theory. This collection heralds a more direct and mutually constructive engagement with current linguistic theories, questions, and methodologies. It achieves this through areal overviews, theoretical chapters, and case studies. The 36 articles are divided between four themes: Foundations, World Englishes and Linguistic Theory, Areal Profiles, and Case Studies. Part I sets out the complex history of the global spread of English. This is followed, in Part II by chapters addressing the mutual relevance and importance of World Englishes and numerous theoretical subfields of Linguistics. Part III offers detailed accounts of the structure and social histories of specific varieties of English spoken across the globe, highlighting points of theoretical interest. The collection closes with a set of case studies that exemplify the type of analysis encouraged by the volume. As attention is focused on innovative work at the interface of dialect description and theoretical explanation, the book is more succinct in its treatment of applied themes, which are given complementary coverage in other works. "--
"This bookfocuses on some features shared by 'Old' and 'New' varieties of English. 'Old' refers here to varieties of English spoken in Britain only, i.e. English English (EngE) and/or British English (BrE). They represent the longest-established varieties of English and are part of the hardcore of the L1 or the 'Inner Circle' of Englishes. 'New' varieties, in this context, are ones that have arisen in colonial or postcolonial contexts (the 'Outer Circle') and also comprise historically L2 varieties, such as Irish English, that have evolved as a result of language shift. This chapter examines three syntactic features that show similar developments in both New and Old varieties: the use of some modal auxiliaries, especially WILL/SHALL, some 'extended' uses of the progressive, and finally, combinations of these two, especially WILL/SHALL + be V-ing. All three display convergent developments that suggest a leading role for the New Englishes rather than the Old varieties"--
It include index pages
Includes bibliographical references and indexes.
Keywords: English language -- Variation -- Great Britain -- Handbooks, manuals, etc; English language -- Spoken English -- Great Britain -- Handbooks, manuals, etc; English language -- Great Britain -- Handbooks, manuals, etc; English language -- History -- Great Britain; English language -- Globalization; LANGUAGE ARTS & DISCIPLINES / Linguistics / General